The Effect of Giving Dry Shrimp with Different Concentration on the Growth of Green Turtle Baby (Chelonia Mydas) in Sukamade Coastal Areas Meru Betiri National Park , Banyuwangi Regency, East Java (Global Journal of Science Frontier Research, 2015)
Turtle's exictence has long been threatened, either by nature or human eativities. The purpose of this research is to determine the effect of giving different feed concentration on the growth of green turtle baby (Chelonia mydas) at the age of 4 days for 5 week treatment period. This research uses experimental method. The material used is green turtle baby (Chelonia mydas) at the age of 4 days. The research was conducted at Sukamade Beach, Banyuwangi. The feed given is dry shrimp 3% and 8% of the weight of biomass. The results of the research indicate that the green turtle baby given dry shrimp with a concentration of 3% has a specific growth rate 1.429 ± 0.074 on average, less than the green turtle baby given dry shrimp with concentration of 8% which has a specific growth rate 1.630 ± 0.192.
Keywords: green turtle baby (chelonia mydas); growth; feed